Geopatrimônio dos municípios de Porto do Mangue e Macau - RN - Silva, Fernando Eduardo Borges da (2022)
Geodiversity is a recent concept academically, emerging and gaining notoriety mainly from the 1990s, its object of study is the abiotic environment of the various landscapes of the earth, listing its values, whether intrinsic (value for mere existence), value economic, scientific, aesthetic, cultural, tourist value and others. Based on the notion of heritage, as an asset of value (inheritance) left to future generations, the discussion about the values of geodiversity supports the idea of heritage of abiotic diversity, of a geoheritage or geoheritage, which in turn establishes methods for the selection of sites with the greatest potential, interest and geological, geomorphological, hydrological, etc. value. For a purpose tangent to geoconservation or geotourism. The geoheritage is subdivided into some branches, with a specific focus on different areas of study as far as geomorphology is concerned, the correspondent is the geomorphological/geomorphoheritage. The present study aims to carry out an inventory and quantification of the places of interest in the geomorphological heritage of Porto do Mangue and Macau/RN. Following the methodology developed by Araújo (2021) with occasional changes, the process of inventorying the places of interest was started, with a total of eight sites with geomorphological potential being identified, namely (Hypersaline Desert, Falésias do Rosado, Dunas do Rosado, Estuário do Rio das Conchas, Camapum Beach, Ponta do Tubarão Estuary, Mangue Seco Dome and Macau Magmatism). Based on the inventory, a quantitative assessment of the sites was carried out, in which all with the exception of the Domo do Mangue Seco were considered as geomorphossites due to their scientific or aesthetic value. The tabulation of the information obtained in the quantitative assessment allowed the construction of a database, regarding the particularities of the abiotic environment of the study area, making it possible to analyze in an integrated or exclusive way the local geomorphological heritage, such as the geomorphological value - ( VGM), in which the Macau Magmatism site obtained the highest degree of relevance, or the general ranking, in which it exhibits the most important geomorphosite in the area, represented by the Ponta do Tubarão Estuary site. Finally, the material developed in the research provides a methodological and procedural database, with the results being able to serve as a basis for the promotion of geotourism, as well as for the creation of areas aimed at the preservation of sites and concomitant geoconservation.